Models of value creation measurement in different manufacturing industry sectors in the Czech Republic - Petr Suchánek; Martin Štěrba (Trends Economics and Management, 2018)
Purpose of the article: The subject of this article is the construction of a model which is able to measure whether an enterprise is creating or destroying value. In the light of our previous research, we are not seeking to create a universal model, instead we want to create a set of special models that consider the specificities of different sectors. Therefore, we have created three models especially for the food industry, engineering and transportation. Methodology/methods: We used the financial analysis, portfolio analysis and logistic regression. Scientific aim: The aim of the article is to construct value-measuring models in various sectors of the manufacturing industry. We start from the premise that it is very difficult to construct a universal model that is able to measure the value in different sectors equally well. Therefore, using the example of three manufacturing industries (namely the food industry, engineering and transportation), we constructed three models and then compared and discussed the differences observed. Findings: The results confirmed that there are significant differences between the models of value creation within the three sectors which we studied. The main difference in each sector is its capital structure. For each model, we selected a different number of indicators using statistical methods to create the optimal model. Conclusions: The first research limitation is that the focus is only on three sectors. As part of further research, it will be necessary to construct different models in other sectors as well. The second limitation of the research is that it focuses purely on finance, which does not allow many options to identify and discuss the internal and qualitative differences of the enterprises and sectors under examination, which could contribute to increasing the accuracy of the model. The model is constructed from publicly available data, which is both a limitation and an advantage.
Keywords: G31; L61; L62; L66; 650; EVA ratio; value creation model; financial analysis; performance; food industry; construction industry; engineering